In vitro antifungal activity of chitosan derived from shrimp co-products against pathogenic fungi isolated in Vietnam - Tran, Long Dinh; Nguyen, Xuan Bach; Phan, Thanh Loc; Nguyen, Quynh Thuong; Nguyen, Thanh Duc; Tran, Truc Thanh; Tran, Van Ty (Vietnam Journal of Biotechnology, 2025)
The global overuse of antibiotics and agrochemicals in Vietnam leads to antibiotic resistance, health risks, and environmental damage. This study evaluates in vitro antifungal properties of different types of shrimp waste-derived chitosan against Vietnamese agricultural fungi as a sustainable alternative to chemical fungicides. Several pathogenic microbe strains were isolated and identified by morphological and molecular gene sequencing: Neoscytalidium dimidiatum causing brown spot on dragon fruit; Fusarium fujikuroi & Fusarium subglutinans causing banana crown rot; Fusarium oxysporum & Fusarium odoratissimum causing banana stem rot; Lasiodiplodia theobromae causing fruit rot & Colletotrichum queenslandicum causing anthracnose on passion fruit; Fusarium equiseti & Fusarium napiforme causing swollen swim bladder on striped catfish. The antifungal properties of several chitosan types were investigated following the inhibition of the fungal mycelial growth method. CTIC15 & OLIC25 demonstrated significant fungal growth inhibition from 90% to 100% at 0.328 g/L to 0.625 g/L for all isolated fungal strains. Chitooligosaccharide COSL02 exhibited an antifungal effect against L. theobromae, F. oxysporum, N. dimidiatum, and F. odoratissimum with inhibition rates from 53.11 ± 2.74% to 100 ± 0.00% at 0.438 g/L to 0.876 g/L. Low molecular weight LV01 displayed broad-spectrum antifungal efficacy, excluding F. subglutinans, with inhibition rates from 74.11 ± 10.36% to 100 ± 0.00% at 0.2 g/L, and above 42.08 ± 5.87% at 0.1 g/L. Medium molecular weight MV01 shared comparable antifungal potency to LV01, except for F. equiseti and N. dimidiatum, with inhibition rates from above 74.09 ± 7.09% to 100 ± 0.00% at 0.2 g/L, and above 58.77 ± 0.87% at 0.1 g/L. This study suggested chitosan (shrimp waste) could serve as an effective and sustainable alternative to chemical fungicides in controlling pathogenic microbes.